Join the Chorus, Avoid the Spotlight: The Effect of Neighborhood and Social Dynamics on Human Rights Organization Shaming. (January 2019) - Bell, Sam R.; Clay, K. Chad; Murdie, Amanda
Which countries are likely to be ignored for their human rights abuses? This article focuses on one particular way that cases of human rights abuse might be overlooked by human rights organizations (HROs): the relative visibility of the state's abusiveness vis-à-vis its geographic and social peers. HROs are more likely to target abusive states that are located in regions with more HRO resources and/or are surrounded by states that demonstrate higher respect for human rights, as these abuses will stand out much more clearly. Further, human rights treaties can be used by abusive states as a form of strategic "social camouflage, " with states trying to minimize the risk of HRO attention by ratifying human rights treaties to look more like their rights-respecting peers. Using a cross-national time-series research design, this article finds much support for the argument: abusive states that "join the chorus" avoid HRO attention.